Examining geography as a predictor of students’ university intentions: a logistic regression analysis - Cooper, Grant; Strathdee, R.; Baglin, J. (2018)
While improving educational aspirations has been positioned by various stakeholders (e.g. governments, researchers, educators) as an important part of increasing higher education participation, there appears to be disagreement in the literature about this relationship. If a key goal of eliciting students’ educational aspirations is to reliably predict future university participation, researchers should choose aspiration measures supported by evidence regarding their predictive validity. In this article, the authors examine students’ university intentions considering past research has demonstrated the relative strength of its predictive validity. The key aim of this article is to investigate if, and to what extent, distance predicts students’ intentions to attend university. Over 9400 Australian students are included in the analysis. Findings indicated students from provincial areas were significantly less likely to report intent to study at university when compared with metropolitan students. Furthermore, remote students were less likely to report an intention to attend university than students in the metropolitan category. Controlling for socio-economic status (SES), as distance increases from an Australian metropolitan area, the likelihood of students reporting intentions to study at university decreases.